Police diplomacy - Kekić Dalibor; Subošić Dane (Međunarodni Problemi)
Police diplomacy is one of the most interesting issues of the contemporary international relations. Sources of this issue comes at the beginning of XX century. Organized criminal and terrorism influenced on appearance of international police cooperation at the end of XIX century. Police cooperation has enlarged last years. Termins police attaché and liason officer are used for the same purpose, but there are four key distinctions between them.